Formulation and Evaluation of Self Emulsifying Drug Delivery System of Lopinavir - Udiwal, Oshin; Gehlot, Narendra; Joshi, Garvita; Jain, Vikas (Journal of Neonatal Surgery, 2026)
Lopinavir (LOP) is a poorly water-soluble antiretroviral drug with limited oral bioavailability. The present study aimed to develop and evaluate liquid and solid self-emulsifying drug delivery systems (SEDDS) to enhance the solubility and dissolution behavior of lopinavir. Preformulation studies revealed a melting point of 104–106 °C and confirmed drug purity and compatibility by FTIR spectroscopy. Solubility screening identified Capmul MCM C8 EP as the most suitable oil, exhibiting a solubility of 75–100 mg/g, while Cremophor RH40 and Labrafil M 2125 CS showed superior emulsification efficiency with percentage transmittance values of 98.32% and 100.20%, respectively. Ternary phase diagram studies demonstrated a broad self-emulsifying region for the Capmul MCM C8–Cremophor RH40–Labrafil M 2125 system, maintaining fine emulsification up to 60% oil concentration. The optimized liquid SEDDS (L2) exhibited a mean globule size of 60.19 ± 3.27 nm in distilled water, 65.23 ± 3.15 nm in simulated gastric fluid, and 61.19 ± 3.15 nm in simulated intestinal fluid, with polydispersity indices below 0.45 and positive zeta potential values ranging from +13.12 to +14.23 mV. The formulation showed excellent robustness to dilution with transmittance values exceeding 98% and no drug precipitation for up to 12 h. In vitro dissolution studies demonstrated rapid drug release, with more than 85% lopinavir released within 20 min and complete drug release within 60 min in all dissolution media. The optimized L-SEDDS was successfully converted into tablet SEDDS (T-SEDDS), which complied with pharmacopeial quality parameters, including hardness (4.5 kg/cm²), friability (0.54%), disintegration time (2 min 45 s), and drug content (99.52 ± 2.56%). The T-SEDDS exhibited complete drug release within 120 min, comparable to the liquid formulation. Stability studies conducted at 40 ± 2 °C/75 ± 5% RH for 3 months showed no significant changes in physical appearance, disintegration time, or drug content. These results demonstrate that SEDDS is an effective strategy for enhancing the oral delivery of lopinavir and offers a promising approach for improving the bioavailability of poorly water-soluble drugs..